2012
DOI: 10.1159/000339965
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes and False-Positive Troponin I in a Patient with Acute Cholecystitis

Abstract: Cardiac troponins are the most sensitive and specific serum markers of myocardial cell injury, but they can also arise without apparent cardiac injury. Besides, acute cholecystitis may be associated with nonspecific ST-T wave changes in electrocardiography (ECG). The signs and symptoms of gallbladder and heart disease may overlap, which can make diagnosis difficult. We describe the case of a 75-year-old woman with clinical features suggestive of acute cholecystitis associated with transient ST segment elevatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
1
18
0
3
Order By: Relevance
“…Previous studies have noted electrocardiographic changes consistent with STEMI with or without cardiac biomarker elevation in patients admitted with acute cholecystitis 6, 7, 8, 9. Upon inspection of coronary arteries by coronary angiography, there were no signs to indicate CAD, ischemia, myocarditis, pericarditis, or coronary spasm.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have noted electrocardiographic changes consistent with STEMI with or without cardiac biomarker elevation in patients admitted with acute cholecystitis 6, 7, 8, 9. Upon inspection of coronary arteries by coronary angiography, there were no signs to indicate CAD, ischemia, myocarditis, pericarditis, or coronary spasm.…”
Section: Discussionmentioning
confidence: 78%
“…Various sources have also reported elevated troponin levels in patients with sepsis, septic shock or systemic inflammatory response syndrome, but the mechanism by which infection causes troponin release is not yet understood [25]. Makaryus et al showed that other sources of circulating antibodies include immunotherapies, vaccinations, or blood transfusions may interfere with these immunoassays as well.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in the complete ANZASM database are most frequently attributed to diagnostic support services with misinterpretation of results, incorrect tests being performed, and results not seen. 8 Possible clinical reasons for the delay in diagnosis in the 10 excluded patients could include the following: acute coronary syndrome mimicking acute biliary pathology, for example, with increased troponin concentration 9 ; lack of right upper quadrant tenderness in one-quarter of elderly patients with acute cholecystitis 10 ; or normal white blood cell count in one-third of elderly patients with acute cholecystitis. 10 The observation that complications in the elderly population are difficult to predict has led to the recent use of the concept of frailty to identify patients at risk.…”
Section: Discussionmentioning
confidence: 99%